Force Plate Gait Analysis and Clinical Results after Tibial Plateau Levelling Osteotomy for Cranial Cruciate Ligament Rupture in Small Breed Dogs - Amimoto, Hirokazu; Koreeda, Tetsuaki; Ochi, Yoshiyuki; Kimura, Ryota; Akiyoshi, Hideo; Nishida, Hidetaka; Miyabayashi, Takayoshi; Beale, Brian S.; Hayashi, Kei; Wada, Naomi (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to evaluate objective limb function using force plate gait analysis after tibial plateau levelling osteotomy (TPLO) in small breed dogs with cranial cruciate ligament rupture (CCLR).Materials and Methods Small breed dogs (15 kg or less) with unilateral CCLR treated with TPLO were evaluated using symmetry index (SI) of peak vertical force (PVF), vertical impulse and vector magnitude at PVF performed preoperatively and at 1, 2, 4 and 6 months postoperatively after routine TPLO surgery.Results Twelve dogs met the inclusion criteria. Hindlimb function was markedly improved after TPLO, with all three postoperative SI significantly higher after a month than preoperative values (p < 0.01). At 2 months after surgery, the SI was nearly normalized to 1.0 (preoperative SI: 0.50 ± 0.20, 0.44 ± 0.19 and 0.51 ± 0.19, and 2 months postoperative SI: 0.92 ± 0.16, 0.90 ± 0.18 and 0.92 ± 0.16 respectively). Complications were noted in two dogs (fibular fracture and a partial implant failure), neither of which required a revision surgery for acceptable functional recovery.Conclusion The objective limb function of the affected hindlimb improved continuously after surgery and reached a near normal value at 6 months after surgery. It was suggested that TPLO for small breed dogs had good outcomes based on force plate gait analysis.
Keywords: cranial cruciate ligament rupture; tibial plateau levelling osteotomy; small breed dogs; postoperative tibial tuberosity width; force plate gait analysis